Penilaian Otentik dalam Pengajaran Membaca pada Tingkat Madrasah Tsanawiyyah - S, Shabilla Washol; Maswani, Maswani (Kalimatuna: Journal of Arabic Research, 2023)
This study aims to determine the application of authentic assessment in learning reading at Madrasah Tsanawiyah Negeri 4, the obstacles teachers face in implementing an authentic evaluation system and their solutions, and student responses to authentic assessments. To analyze this problem, the researcher used the descriptive analysis method. The method that the researchers uses to take the sample is the purposive sampling method. The data were collected from the results of questionnaires and interviews. Therefore, the data was analyzed, and then the results were in descriptive form by looking at the value data table and the student response table. It was found that students had good authentic assessments of reading skills supported by methods and media provided by the teacher. The researchers concluded that many students had accomplished minimum criterion. The obstacles are the lack of lessons time and online learning.